Frontline Science: LPS‐inducible SLC30A1 drives human macrophage‐mediated zinc toxicity against intracellular Escherichia coli. Issue 2 (22nd May 2020) - Stocks, Claudia J.; von Pein, Jessica B.; Curson, James E.B.; Rae, James; Phan, Minh‐Duy; Foo, Darren; Bokil, Nilesh J.; Kambe, Taiho; Peters, Kate M.; Parton, Robert G.; Schembri, Mark A.; Kapetanovic, Ronan; et al.
Abstract: TLR‐inducible zinc toxicity is an antimicrobial mechanism utilized by macrophages, however knowledge of molecular mechanisms mediating this response is limited. Here, we show that E. coli exposed to zinc stress within primary human macrophages reside in membrane‐bound vesicular compartments. Since SLC30A zinc exporters can deliver zinc into the lumen of vesicles, we examined LPS‐regulated mRNA expression of Slc30a / SLC30A family members in primary mouse and human macrophages. A number of these transporters were dynamically regulated in both cell populations. In human monocyte‐derived macrophages, LPS strongly up‐regulated SLC30A1 mRNA and protein expression. In contrast, SLC30A1 was not LPS‐inducible in macrophage‐like PMA‐differentiated THP‐1 cells. We therefore ectopically expressed SLC30A1 in these cells, finding that this was sufficient to promote zinc‐containing vesicle formation. The response was similar to that observed following LPS stimulation. Ectopically expressed SLC30A1 localized to both the plasma membrane and intracellular zinc‐containing vesicles within LPS‐stimulated THP‐1 cells. Inducible overexpression of SLC30A1 in THP‐1 cells infected with the Escherichia coli K‐12 strain MG1655 augmented the zinc stress response of intracellular bacteria and promoted clearance. Furthermore, in THP‐1 cells infected with an MG1655 zinc stress reporter strain, all bacteria contained within SLC30A1‐positive compartments were subjected to zinc stress. Thus, SLC30A1 marks zinc‐containing compartments associated with TLR‐inducible zinc toxicity in human macrophages, and its ectopic over‐expression is sufficient to initiate this antimicrobial pathway in these cells. Finally, SLC30A1 silencing did not compromise E. coli clearance by primary human macrophages, suggesting that other zinc exporters may also contribute to the zinc toxicity response. Graphical Abstract: The zinc transporter SLC30A1 is LPS‐inducible in human macrophages and can deliver a zinc toxicity response against intracellular Escherichia coli .